Wheat Cost-Return Budget in South Central Kansas - Warmann, Gerald W. (My University, 1996)
This publication projects a budget that reflects expected income and costs based on wheat production in south central Kansas.
MF574_1996_10
Keywords: MF574; Economics; Crops; MF